2019
DOI: 10.1155/2019/3602585
|View full text |Cite
|
Sign up to set email alerts
|

Compliance to Iron-Folic Acid Supplementation and Its Association with the Number of ANC Visits in Ethiopia: Systematic Review and Meta-Analysis

Abstract: Background. The World Health Organization recommended that 80% of communities in all countries should receive the standard dose of iron folic acid. But, in Ethiopia, this target was not yet achieved. The compliance of iron folic acid was also variable across each district. Therefore, the aim of this study was to assess women compliance with iron-folic acid supplementation and its association with a number of antenatal care visits in Ethiopia using systematic review and meta-analysis, 2018. Methods. In the curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 38 publications
1
14
1
Order By: Relevance
“…Previously published systematic reviews used different cutoffs to define adherence to micronutrient supplements in pregnancy, which varied from 70% 48 to 95% 7 of the recommended daily supplementation dose or was defined as the intake of micronutrient tablets for 90 days or more. 49 Given this variability in the definition of adherence and the criticism of using a specific threshold (which could not be proved to be linked to clinical outcomes 50 ), in the present work, we decided to report adherence to the micronutrient supplementation regimen as measured and defined by the study authors. Consequently, we found that the included studies used a wide range of methods to measure adherence (from prevalidated questionnaires to self-reported recall or pill counting) and to define adherence (from a minimum number of tablets taken over a certain period of time to the use of behavior scales).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously published systematic reviews used different cutoffs to define adherence to micronutrient supplements in pregnancy, which varied from 70% 48 to 95% 7 of the recommended daily supplementation dose or was defined as the intake of micronutrient tablets for 90 days or more. 49 Given this variability in the definition of adherence and the criticism of using a specific threshold (which could not be proved to be linked to clinical outcomes 50 ), in the present work, we decided to report adherence to the micronutrient supplementation regimen as measured and defined by the study authors. Consequently, we found that the included studies used a wide range of methods to measure adherence (from prevalidated questionnaires to self-reported recall or pill counting) and to define adherence (from a minimum number of tablets taken over a certain period of time to the use of behavior scales).…”
Section: Discussionmentioning
confidence: 99%
“…Defining and quantifying adherence, as well as providing an estimate of the effect size of an intervention on adherence for a pooled body of evidence, is challenging. Previously published systematic reviews used different cutoffs to define adherence to micronutrient supplements in pregnancy, which varied from 70% 48 to 95% 7 of the recommended daily supplementation dose or was defined as the intake of micronutrient tablets for 90 days or more 49 . Given this variability in the definition of adherence and the criticism of using a specific threshold (which could not be proved to be linked to clinical outcomes 50 ), in the present work, we decided to report adherence to the micronutrient supplementation regimen as measured and defined by the study authors.…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of compliance to iron supplementation in our study was low compared to other studies. A systematic review and Meta analysis study by Yineger Workineh et al showed that the overall prevalence of compliance with iron-folic acid supplementation was 43.63% [7]. Another systematic review and Meta analysis research by Desta et al also showed that 46.15% of Ethiopian women had adhered to iron and folic acid supplementation [14].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a study conducted in eight rural Woredas of Ethiopia revealed that, those women who had less than four ANC visits were less likely adhere to iron supplementation [15]. A Meta analysis studies also indicated that having of four or more ANC visits increased compliance of mothers to iron supplementation [7,14]. The possible reason could be that those mothers who had repeated ANC might be exposed to repeated counseling on anemia and the benefits of iron supplementation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation